2012
DOI: 10.1364/ao.51.002856
|View full text |Cite
|
Sign up to set email alerts
|

Resonator fiber optic gyro employing a semiconductor laser

Abstract: Resonator fiber optic gyro (RFOG) based on the Sagnac effect has the potential to achieve the inertial navigation system requirement with a short sensing coil. Semiconductor laser is one of the key elements for integration and miniaturization of the RFOG. In this paper, an RFOG employing a semiconductor laser is demonstrated. The model of the laser frequency noise induced error in the RFOG is described. To attenuate the laser frequency noise induced error, active frequency stabilization is applied. An online l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Jin et al described the model of the frequency stabilization loop in the counterclockwise (CCW) direction in detail [4]. The frequency stabilization loop is composed of a laser, a frequency discriminator and a PI controller, as shown in Figure 1.…”
Section: Theory and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al described the model of the frequency stabilization loop in the counterclockwise (CCW) direction in detail [4]. The frequency stabilization loop is composed of a laser, a frequency discriminator and a PI controller, as shown in Figure 1.…”
Section: Theory and Simulationmentioning
confidence: 99%
“…Laser frequency noise is the main one of the reciprocal noises. Z. Jin et al demonstrated the influence of the laser frequency noise in the RFOG and proposed an effective method of a frequency stabilization loop based on the proportional integrator (PI) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The double/hybrid phase modulation technique was also demonstrated theoretically and experimentally [19,20]. The modulation technique based on the absorption feature can realize carrier suppression; however, the modulation frequency is limited by the FWHM of the reference cavity, which is not suitable for 1/f noise suppression when the FWHM is relatively small [21]. The Pound-Drever-Hall (PDH) technique based on the dispersion feature can solve this problem [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The rotation rate sensitivity of 0.28 deg∕h (10 s integration time) is achieved by Imai et al, using a highly coherent laser diode module [18]. Jin et al demonstrated an RFOG employing a distributed feedback laser diode, a bias stability of 9.5 deg∕h for the integration time 10 s in an hour was obtained [19]. A fiber ring resonator (FRR) is used to sense the angular velocity in the RFOG.…”
Section: Introductionmentioning
confidence: 99%